Pengaruh Sistem Informasi Sumber Daya Manusia Terhadap Kinerja Pegawai, Evaluasi Kerja Pegawai Sebagai Variabel Intervening Pada Lingkup Satuan Kerja Perangkat Daerah Kabupaten Tojo Una – Una - Zulkifli T; Arifin Arifin; Rahmisyari Rahmisyari (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
This research aims to determine the HR information system on employee performance through employee work evaluation. This research was conducted within the scope of the Tojo Una - Una Regency Regional Work Unit. The research method used is quantitative with a survey approach. Basic data was collected through distributing questionnaires to a total of 97 research samples. The data analysis technique used is SEM-PLS Structural Equality Modeling. The results of this research show that the HR information system has a positive and significant effect on employee performance through job evaluation. Thus, the conclusion that can be drawn from this study is: to increase the influence of the HR information system on employee performance through job evaluation, by following all procedures and regional regulations by paying attention to the stages that have been implemented by the SKPD.